(untitled) (Devenires, 2003)
This paper, facing biomedical scientific advances, changes between medical-patient, kind of State and citizen condition, as well as different judgments about suicide, voluntary Death problem, or not when the patient cannot decide, according Dworkin’s distinction between experience interests and critical interests. After reasons of those who support euthanasia and those who not are some reflections in sense of not avoid ill’s will, always tacking care of prudence.